ATIM-10. CLINICAL PREDICTORS OF RESPONSE FOR RECURRENT/REFRACTORY GLIOBLASTOMA MULTIFORME (GBM) AND ANAPLASTIC ASTROCYTOMA (AA, WHO GRADE III) PATIENTS TREATED WITH THE ANTI-TGFß2 RNA THERAPEUTIC OT-101. (11th November 2019) - Qazi, Sanjive; Nam, David; Hwang, Larn; Trieu, Vuong; Uckun, Fatih
Abstract: BACKGROUND: OT-101 is a first-in-class αTGF-ß2 RNA therapeutic and exhibits significant single-agent activity in patients with recurrent/refractory (R/R) GBM and AA. Here we report significant predictors of best overall response (BOR = CR, PR, stable disease >6 months) and improved OS for R/R GBM and AA patients after treatment with OT-101 on the Phase II study NCT00431561. METHODS: A generalized linear model (GLM; Binomial distribution, logit function link function) was fitted to explore several clinical parameters as potential predictors for BOR. The parametric survival model fitted the time to death using linear regression to predict improved OS. The best fit model was chosen utilizing both Akaike information criterion (AIC) and Bayesian information criterion (BIC) from assessing Weibull, lognormal, exponential, Fréchet, and loglogistic distributions of the survival probabilities (JMP 10.02, SAS, Cary NC). RESULTS: In both models, time from last chemo-/radiation therapy, time from first diagnosis and baseline hematological measurements (ALC, ANC and WBC) were removed from the model as they lacked significant predictive value. The final GLM (chi-square value = 39.7, df = 12, P< 0.0001) and OS (chi-square value = 56.0, df = 12, P< 0.0001) models contained 7 predictor variables measured in 67 evaluable patients: Baseline Karnofsky performance scale (KPS) score; composition of previous therapy; cancer subtype; steroid use; total OT-101 dose; age; and baseline 3D tumor volume for the target lesion. Three significant predictors were identified: Baseline KPS score (P[BOR] = 0.011; P[OS] = 0.0004), cancer subtype (P[BOR] = 0.017, P[OS] = 0.036) and steroid use (P[BOR] = 0.0067, P[OS] = 0.0022). CONCLUSION: Being an AA patient rather than a GBM patient, having a higher baseline KPS score, receiving either no steroids or short-term steroids during management of AE are associated with BOR and improved OS for R/R GBM/AA patients treated with OT-101 as a single agent.